1998
DOI: 10.1007/pl00005171
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition by ethanol of excitatory amino acid receptors in rat locus coeruleus neurons in vitro

Abstract: Intracellular recordings were made in a pontine slice preparation of the rat brain containing the nucleus locus coeruleus (LC). In a first series of experiments, various parameters of spontaneous action potentials were evaluated. It turned out that ethanol (100 mM) does not alter the firing rate, the spike amplitude and the afterhyperpolarization following a spike. In subsequent experiments, the generation of action potentials was prevented by passing continuous hyperpolarizing current via the recording electr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
18
1
1

Year Published

2000
2000
2023
2023

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 39 publications
4
18
1
1
Order By: Relevance
“…Ethanol inhibition of NMDA receptor activation in RVLM neurons was detected not only during systemic administration but also during bath superfusion in a single neuron in vitro. The concentrations used in our in vitro electrophysiological study were similar to the effective concentrations reported for various neurons in slice preparations [18,21,30,33]. It is interesting to note the differences in ethanol potency between the inhibitions of NMDA-induced pressor effects in vivo and the NMDA-mediated inward currents in vitro.…”
Section: Discussionmentioning
confidence: 49%
See 1 more Smart Citation
“…Ethanol inhibition of NMDA receptor activation in RVLM neurons was detected not only during systemic administration but also during bath superfusion in a single neuron in vitro. The concentrations used in our in vitro electrophysiological study were similar to the effective concentrations reported for various neurons in slice preparations [18,21,30,33]. It is interesting to note the differences in ethanol potency between the inhibitions of NMDA-induced pressor effects in vivo and the NMDA-mediated inward currents in vitro.…”
Section: Discussionmentioning
confidence: 49%
“…Since the initial report by Lovinger et al [20] on the ability of ethanol to inhibit NMDA-receptor-mediated currents in the mouse hippocampus, the effects of ethanol on NMDA receptor activation have been examined extensively in various neuronal preparations from CNS and cultured neurons. In rats, for example, acute exposure to ethanol in vitro inhibited NMDA-mediated responses in the nucleus accumbens [29], the hippocampus [21], the locus ceruleus [30], the cortical neurons [25], the spinal motor neurons [40] and the SPN [18]. In contrast, chronic ethanol treatment resulted in supersensitivity to NMDAmediated events, which are thought to be involved in the development of both ethanol tolerance and subsequent withdrawal hyperexcitability [8,36].…”
Section: Introductionmentioning
confidence: 99%
“…EtOH also inhibits the function of AMPARs, and effects can be seen at concentrations as low as 10 mM (Akinshola 2001;Akinshola et al 2003;Dildy-Mayfield and Harris 1992;Möykkynen et al 2003;Nieber et al 1998;Wirkner et al 2000). In neurons from the brain, EtOH generally shows lower potency for inhibition of AMPARs in comparison to NMDARs (Frye and Fincher, 2000;Lovinger et al 1989;Lovinger 1995).…”
Section: Ligand-gated Ion Channels and Postsynaptic Ethanol Effectsmentioning
confidence: 99%
“…For example, this method was recently used to demonstrate that, in locus coeruleus neurons recorded in pontine slices, ethanol significantly inhibits EPSPs while having no significant effects on IPSPs or membrane properties of these cells (Nieber et al, 1998). Evans and colleagues (2000) recently used intracellular recordings in inferior colliculus neurons to characterize hyperexcitability associated with ethanol withdrawal.…”
Section: Intracellular (Sharp) Electrode Recordingmentioning
confidence: 99%